A concise route to functionalized benzofurans directly from gem-dibromoalkenes and phenols1. Issue 80 (2nd September 2015) - Rao, Maddali L. N.; Dasgupta, Priyabrata
<x xml:space="preserve">Abstract</x> A tandem strategy for the construction of benzofuran motifs has been developed directly from gem-dibromoalkenes and phenols under palladium-catalyzed conditions.